A Chitosan-Based Fluorescent Probe Combined with Smartphone Technology for the Detection of Hypochlorite in Pure Water - Xushuo Yuan; Wenli Zhang; Li Liu; Yanfei Lin; Linkun Xie; Xijuan Chai; Kaimeng Xu; Guanben Du; Lianpeng Zhang (Molecules, 2023)
Using chitosan as a raw material, 1,8-naphthimide as the fluorescent chromophore, and sulfur-containing compounds as the recognition groups, a novel naphthimide-functionalized chitosan probe, CS-BNS, for the detection of ClO− was successfully synthesized. The modification of chitosan was verified by SEM, XRD, FTIR, mapping, 13C-NMR, TG and the structure of the probe molecule was characterized. The identification performance of the probes was studied using UV and fluorescence spectrophotometers. The results show that CS-BNS exhibits a specific response to ClO− based on the oxidative reaction of ClO− to the recognition motifs, as well as a good resistance to interference. And the probe has high sensitivity and fast response time, and can complete the detection of ClO− in a pure water system within 60 s. The probe can also quantify ClO− (y = 30.698x + 532.37, R2 = 0.9833) with a detection limit as low as 0.27 μM. In addition, the combination of the probe with smartphone technology enables the visualization and real-time monitoring of ClO−. Moreover, an identification system for ClO− was established by combining the probe with smartphone technology, which realized the visualization and real-time monitoring of ClO−.